2022
DOI: 10.1002/oby.23380
|View full text |Cite
|
Sign up to set email alerts
|

Constant light exposure alters gut microbiota and short‐/medium‐chain fatty acids and aggravates PCOS‐like traits in HFD‐fed rats

Abstract: Objective This study investigated the effects of constant light exposure on polycystic ovary syndrome (PCOS)‐like endocrine and metabolic changes in high‐fat diet (HFD)‐fed rats and to elucidate the related microbiotic mechanisms. Methods A total of 32 female Sprague‐Dawley rats were divided into four groups (n = 8 each): rats on a normal chow diet with standard light‐dark cycle, rats on a normal chow diet with constant light exposure, rats on an HFD with standard light‐dark cycle, and rats on an HFD with cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 47 publications
(59 reference statements)
1
1
0
Order By: Relevance
“…Although the Firmicutes/Bacteroidetes (F/B) ratio as a marker for assessing gut microbiota health remains a topic of debate, accumulating evidence, including our own research, supports its potential utility. Our study revealed a positive correlation between MPA and an increased F/B ratio, consistent with previous investigations conducted by Yue et al (2022) and Hong et al (2020) . In their respective studies, mice were exposed to standard light–dark cycles and constant light for 16 weeks, with the constant light group exhibiting a higher relative abundance of Firmicutes and a lower relative abundance of Bacteroidetes .…”
Section: Discussionsupporting
confidence: 93%
“…Although the Firmicutes/Bacteroidetes (F/B) ratio as a marker for assessing gut microbiota health remains a topic of debate, accumulating evidence, including our own research, supports its potential utility. Our study revealed a positive correlation between MPA and an increased F/B ratio, consistent with previous investigations conducted by Yue et al (2022) and Hong et al (2020) . In their respective studies, mice were exposed to standard light–dark cycles and constant light for 16 weeks, with the constant light group exhibiting a higher relative abundance of Firmicutes and a lower relative abundance of Bacteroidetes .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found that the Prevotella genus was the main feature discriminating bacterial communities in the CI group. Yue et al also found that Prevotella was enriched in the group of rats with continuous light exposure and positively correlated with serum testosterone and IL-6 levels [ 45 ]. Li et al showed that Prevotella is a common pre-hypertensive and hypertensive microbial signature that may play an important role in hypertension by triggering an inflammatory response [46].…”
Section: Discussionmentioning
confidence: 99%